2001
DOI: 10.1046/j.1460-9592.2001.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Ancillary Tools in Pacemaker and Defibrillator Lead Extraction Using a Novel Lead Removal System

Abstract: A previous report described our preliminary experience with a highly successful pacing lead removal system (VasoExtor). Extending this experience, we found it necessary to use additional tools to enhance the success of percutaneous lead extraction with this system. In the present series, we used the standard locking stylets (S and K), and recently, one newer type of stylet (Magic) over the last 3 years in 34 patients to extract 48 pacemaker leads in 31 patients and 3 defibrillator (ICD) leads in 3 patients. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Previous studies have addressed the issue of NTL extraction 11–14 , 19–22 . Costa et al 15 recently described their experience using LASER for extraction of 56 relatively long‐standing pacemaker and NTLs (mean implantation time 7.5 years), 9 of which were ICD leads.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have addressed the issue of NTL extraction 11–14 , 19–22 . Costa et al 15 recently described their experience using LASER for extraction of 56 relatively long‐standing pacemaker and NTLs (mean implantation time 7.5 years), 9 of which were ICD leads.…”
Section: Discussionmentioning
confidence: 99%
“…Initially until the mid‐1990s, an extraction rate of only 80% of all pacemaker and ICD leads was attained using special extraction guidewires and locking stylets 36 . In 1998, the introduction of the laser extraction systems and further ancillary tools (additional femoral approach using lasso and pigtail catheters and bioptomes) allowed complete lead removal in 90–95% of cases and partial lead removal in up to 97% of all leads 37–39 . At the same time, the risk of severe complications including pericardial tamponade mandating emergency thoracotomy and death decreased from 8.1% to 4.1% 38 .…”
Section: Lead Extractionmentioning
confidence: 99%
“…In all of these studies most leads were pacemaker leads. The proportion of ICD leads only was 6% to 18% in these studies 14–19 . The study with the largest number (n = 138) of extracted ICD leads showed an overall complication rate of 7% 20 .…”
Section: Discussionmentioning
confidence: 69%
“…The success rate of lead extraction has significantly improved and the risk has diminished over the last 5 to 10 years. The introduction of laser extraction systems and further ancillary tools has allowed complete lead removal in 89% to 97% of cases 14–20 . At the same time, the risk of severe complications decreased from 8.1% to 3.3% 14–17,19–21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation